Quality of Early Intensive Behavioral Intervention as a Predictor of Children's Outcome. Issue 6 (November 2021) - Långh, Ulrika; Perry, Adrienne; Eikeseth, Svein; Bölte, Sven
Research has directed surprisingly little attention to the quality of Early Intensive Behavioral Intervention (EIBI) in autism spectrum disorder (ASD) as a potential predictor of outcome. Therefore, using a preschool delivery model within a sample of 30 children, we examined the predictive power of EIBI quality on treatment outcome. EIBI quality was assessed at baseline by the York Measure of Quality of Intensive Behavioral Intervention (YMQI) and treatment outcome was evaluated after a period of 4 to 6 months using a battery of behavioral tests and scales to evaluate treatment success. Multinomial logistic regressions demonstrated that general EIBI quality predicted clinically significant change at follow-up. Particularly improvements in basic language and learning skills and global clinical impression were observed. Specific quality indicators that influenced overall treatment success were treatment organization, teaching level and differential reinforcement. In addition to previously examined predictors of EIBI treatment effects, such as child characteristics and intervention quantity, our findings highlight the importance of adequate EIBI quality assurance.